Insights on Renal Profiles of Iraqi Patients With Type II Diabetes - Abd Al-Ghanny, Rand Jalal; Atta, Safaa Ehssan; Omran, Hussein Hatam; Salman, Isam Noori (University of Thi-Qar Journal of Science, 2025)
Diabetic kidney disease, also known as diabetic nephropathy, is a serious complication that affects around 40% of individuals with diabetes. It stands as the primary cause of chronic kidney disease (CKD) on a global scale. There is an urgent need for widespread innovation to improve health outcomes for patients with diabetic kidney disease, and this will involve predicting the prevalence of renal impairment in diabetic patients.800 patients (312 males and 488 females) with Diabetes Mellitus Type II were enrolled in this cross-sectional study age range from (30-65). All patients were asked to fast for 8-12 hours, and All routine investigating assays (FBG, lipid profile, RFT, HBA1c). eGFR determined by calculator program. The eGFR was classified according to National Kidney Found. The study indicates that hyperglycemia does not affect serum urea levels, so it may not be useful in evaluating renal function for DM. The decline in eGFR is linearly linked with an increased risk of Kidney disease (End Stage. Once the progressive eGFR reduction has commenced, it is crucial to effectively manage the disease process driving this decline. The glomerular filtration rate (GFR) serves as the cornerstone for many of the kidney's regulatory functions and is widely regarded as the most comprehensive indicator of renal function. We recommended that every request for blood creatinine concentration be computed, and an eGFR should be provided using the (CKD-EPI) method.